The geomorphology of Dronning Louise Land - Lister, H.; Wyllie, P. J. (Meddelelser om Grønland, 1957)
The solid geology and morphology of the landscape is described and a hypothesis of the process of advance and recession of the ice is postulated. Stages of glacial recession are constructed in north Dronning Louise Land and approximate dates given to these stages.